AB0445 Ocular Posterior Segment Findings in Antiphospholipid Syndrome. (15th July 2016) - Kucukkomurcu, E.; Unal, A.U.; Esen, F.; Ozen, G.; Diresekeneli, H.; Kazokoglu, H.
Abstract : Background: Antiphospholipid Syndrome (APS) can affect all vessels in the body. Ocular complications are seen most commonly in posterior segment of the eye in these patients. The purpose of this study is to evaluate the posterior segment signs in APS patients and to compare these signs between Primary APS, Secondary APS and Systemic Lupus Erythematosus (SLE) patients without APS. Methods: We have included 11 Primary APS, 2 Sjogren's Syndrome/ 27 SLE patients diagnosed as Secondary APS and 29 SLE patients without APS followed at Marmara University, Division of Rheumatology Outpatient Clinics in this study. All of the patients had a detailed ophthalmological examination, including dilated fundus examination and color fundus imaging. 10 patients with Primary Antiphospholipid Syndrome, 23 patients with Secondary APS and 23 patients with SLE had fundus fluorescein angiography imaging. Results: Mean age of the patients was 34.8±12.5 years in Primary APS, 38.3±11.1years in Secondary APS and 38.3±10.9 years in SLE group. In Primary APS 45.5% of patients had venous thrombosis, 45.5% had arterial thrombosis and 72.7% had obstetric complications. In Secondary APS, 44.8% patients had venous thrombosis, 27.6% had arterial thrombosis and 72.4% had obstetric complications. Venous tortuosity was observed in 6 eyes of 3 patients in Primary APS group and 8 eyes of 4 patients in Secondary APS group. One patient with Secondary APS had bilateral branch retinal arterial occlusion. The most common ocular finding of the FFA was pigment epithelial window defect and was observed totally in 19 eyes of 12 patients. There was no statistically significant difference of ocular findings between the Primary APS, Secondary APS and SLE patients. Conclusions: In this study, ocular posterior segment findings of Primary APS had been observed less commonly than previous studies. The lower prevalence of ocular complications in this study can be the result of early diagnosis and better control of relapses in these patients. Disclosure of Interest: None declared